FAKTOR-FAKTOR PENYEBAB DAN SOLUSI KEGAGALAN LAYANAN PENDIDIKAN TINGGI DI MALANG RAYA: SUATU STUDI KASUS - Imam Hanafi; Suryadi Suryadi; Sukanto Sukanto; Andy Fefta Wijaya; Choirul Saleh (Smart Education, 2022)
Quality education must be included in a comprehensive education system under applicable education laws. The definition of good service quality must pay attention to and be centered on efforts to fulfill customer needs and desires and the accuracy of delivery to balance customer expectations. This study aimed to identify the factors causing the failure of education services in Malang Raya and their solutions. Several data collection techniques were used in this study, including interviews, observation, and documentation. In this study, the main instrument was the researcher himself, who was supported by an interview guide, file notes, and writing instruments. This study uses descriptive data analysis, which aims to describe, explain and explain in detail and systematically about the actual situation, which will then draw a conclusion and finally be able to answer the problems raised in the formulation of the problem. In this study, it was found that the factors causing the failure of educational services in Malang Raya, among others: 1) There is no optimal collaboration between stakeholders, 2) There are still providers of subscription education services that collect tuition fees, 3) Supervisory human resources, 4) An effective supervision system. less than optimal, 5) Inadequate facilities and infrastructure, and 6) Miss Orientation.